Comparison of BISAP and Ranson’s score for predicting severe acute pancreatitis and establish the validity of BISAP score - Aggarwal, Amulya; Mathur, Alok V.; Verma, Ram K.; Gupta, Megha; Raj, Dheeraj (International Surgery Journal, 2020)
Background: Pancreatitis can lead to serious complications with severe morbidity and mortality. So an early, quick and accurate scoring system is necessary to stratify the patients according to their severity so as to enable early initiation of required management and care. Scoring system commonly used have some drawbacks. This study aimed to compare bedside index for severity in acute pancreatitis (BISAP) and Ranson’s score to predict severe acute pancreatitis and establish the validity of a simple and accurate clinical scoring system for stratifying patients. Methods: This is a prospective comparative study on 100 patients diagnosed with acute pancreatitis admitted in department of general surgery. Parameters included in the BISAP and Ranson’s criteria were studied at the time of admission and after 48 hours. Result of these two were compared with that of revised Atlanta classification. Results: As per the BISAP score, the sensitivity and specificity were 95.8 % (95% CI, 76.8-99.8), 94.7 % (95% CI, 86.3-98.3) whereas positive likelihood ratio, negative likelihood ratio 18.21 (95% CI, 6.9-47.44), 0.04 (95% CI, 0.01-0.30) and accuracy was 95 % (95% CI, 88.72%-98.36%). On using Ranson’s score, the sensitivity and specificity were 91.6 (95% CI, 71.5-98.5) and 89.4 (95% CI, 79.8-95) with a positive predictive value 8.71 (95% CI, 4.47-18.96) and negative predictive value of 0.09 (95% CI, 0.02-0.35) and accuracy of 90% (95% CI, 82.38%-95.10%).. Conclusions: BISAP score outperformed Ranson’s score in terms of Sensitivity and specificity of prediction of severe pancreatitis. The authors recommend inclusion of BISAP Scoring system in standard treatment protocol of management of acute pancreatitis.